Black liberation in Kentucky : emancipation and freedom, 1862-1884 - Howard, Victor B. (The University Press of Kentucky, 2010)
Kentucky occupied an unusual position with regard to slavery during the Civil War as well as after. Since the state never seceded, the emancipation proclamation did not free the majority of Kentucky's slaves; in fact, Kentucky and Delaware were the only two states where legal slavery still existed when the thirteenth amendment was adopted by Congress. Despite its unique position, no historian before has attempted to tell the experience of blacks in the Commonwealth during the Civil War and Reconstruction. Victor B. Howard's Black Liberation in Kentucky fills this void in the history of slavery.